Efektivitas Gamifikasi Berbasis Quizizz Terhadap Minat Belajar dan Hasil Belajar Kognitif pada Pembelajaran Sejarah Kebudayaan Islam - M. Dahlan R; Keisya Fajrina (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This research is motivated by the low interest in learning and the low cognitive learning outcomes of students in the subject of Islamic Cultural History (SKI) due to the use of still-conventional learning media. One innovation that can be applied is Quizizz-based gamification, which integrates game elements into the learning process to increase student engagement. This study aims to analyze the effectiveness of Quizizz-based gamification in increasing students' learning interest and cognitive learning outcomes in SKI learning. The research uses a quantitative approach with a quasi-experiment method through a Nonequivalent Control Group Design. The research sample comprised 90 students in class VII at MTs Al-Islamiyah Ciledug, consisting of 45 students in the experimental class and 45 in the control class. Data were collected using a Likert-scale learning-interest questionnaire and cognitive learning outcome tests, administered as pre-tests and post-tests. They were then analyzed using N-Gain and Multivariate Analysis of Variance (MANOVA). The results showed that Quizizz-based gamification was effective in increasing learning interest, with an average N-Gain of 0.7403 (high category), and cognitive learning outcomes, with an average N-Gain of 0.5724 (medium category). The MANOVA results also showed a significant simultaneous influence on both variables (Wilks' Lambda, Sig. = 0.000 < 0.05). Thus, Quizizz-based gamification is recommended as an innovative learning medium that can create SKI learning that is more interactive, interesting, and effective in improving learning quality.